Is it practical to uphold both resilience and sustainability of supply chains using closed-loop supply chain models considering circular economy? An empirical investigation from Kenya - Mary Aming'a; Reuben Marwanga; Jonathan Annan (Cogent Business & Management, 2024)
This paper investigates the practicality of upholding supply chains' resilience and sustainability using six aspects of closed-loop supply chain models considering circular economy (CLSMs). A plant-level survey was utilised to test the influence of CLSMs on resilience sustainability. A proposed research model and hypotheses are tested using cross-sectional face-to-face and e-mail survey data collected from manufacturing firms in Kenya. Structural equation modelling is used to test the proposed hypotheses. Cleaner production exhibits more influence on resilient sustainability on both economic and social sustainability, where the Japanese 5S approach is the most prevalent in cleaner production. Green procurement combined with design for the environment shows a positive effect on environmental sustainability, and reverse logistics shows a positive effect on resilience, unfolding the importance of devising CLSMs strategies for building both resilience and sustainability. Surprisingly, green logistics did not affect any of the resilient sustainability dimensions and reverse logistics on sustainability. These results reveal the practicality of upholding supply chains' resilience and sustainability through CLSMs. While few studies test the direct link between CLSMs and resilient sustainability, this study is significant in the upstarting of such investigations, more so from an empirical perspective. This study contributes to extant literature, practice, and policy by showing the importance of building both resilience and sustainability of supply chains using CLSMs and adopting trade-offs as starting points as economies walk towards points of balance. From a policy perspective, this study points out the need for stringent CLSMs policy measures towards resilience and sustainability, more so in Sub-Saharan African manufacturing contexts.
Keywords: 650; Closed-loop; green; resilience; supply chain and sustainability